The effect of board of directors characteristics, audit committee characteristics and executive committee characteristics on firm performance in Oman: An empirical study - Al-Matari, Ebrahim Mohammed; Al-Swidi, Abdullah Kaid; Fadzil, Faudziah Hanim (Canadian Center of Science and Education, 2014)
This study is an attempt to achieve the main objective by examining the association between the board of director’s characteristics, audit committee characteristics and the executive committee characteristics and the performance of the Oman companies.This study used many assumptions to test the relationship between independent variables and dependent variable as discussed in the section explaining the study method.The data comprised of 162 non-financial companies because financial and non-financial companies employ different methods and they have different structures.As this study attempts to bridge the gap in the existing literature by investigating the association between corporate governance mechanisms and firm performance in the emerging market of Oman, it focuses on adding new important variables of corporate governance mechanisms like board change, the role of secretary on the board, the legal counsel and the executive committee characteristics that improve firm performance.The findings indicated a significantly positive relationship between board size, board meeting, audit committee independence and executive committee independence, and the Tobin`s Q. On the other hand, board independence and legal counsel are significantly and negatively related to Tobin`s Q. Moreover, a positive but insignificant relationship is found between CEO tenure, CEO compensation, audit committee size, and the firm performance (Tobin`s Q). Furthermore, board change, the role of the secretary on the board, audit committee meeting, executive committee size and executive committee meeting are revealed to have a negative but insignificant association with firm performance (Tobin`s Q). Finally, this study provides recommendations for future research.